2013
DOI: 10.4081/gh.2013.81
|View full text |Cite
|
Sign up to set email alerts
|

Does altitude moderate the impact of lithium on suicide? A spatial analysis of Austria

Abstract: Abstract. Suicide, the tenth leading cause of death worldwide, is a complex phenomenon. Models aiming to explain the interaction of ambient variables such as socioeconomic factors, lithium content of drinking water and altitude are poorly developed. While controlling for several risk factors, this research bridges two different, but complementary research lines by investigating statistically the relationship on suicide mortality between lithium levels in drinking water in response to altitude above sea level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 34 publications
1
45
2
1
Order By: Relevance
“…Regional variation in suicide rates in the United States correlate directly with state peak elevation (Haws et al, 2009) and county elevation , despite the decrease in overall mortality rates with altitude . The link between suicide and altitude of residence is also documented in Austria (Helbich et al, 2013) and South Korea . Depression is strongly associated with suicide in the developed world (Henriksson et al, 1993), and mortality by suicide is highly linked to unresolved depression ( Joiner et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Regional variation in suicide rates in the United States correlate directly with state peak elevation (Haws et al, 2009) and county elevation , despite the decrease in overall mortality rates with altitude . The link between suicide and altitude of residence is also documented in Austria (Helbich et al, 2013) and South Korea . Depression is strongly associated with suicide in the developed world (Henriksson et al, 1993), and mortality by suicide is highly linked to unresolved depression ( Joiner et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…In the recent past, epidemiological studies have attempted to correlate lithium in drinking water and suicide prevalence [138,139]. Studies have revealed a marginal but notable decrease in suicide rates with increased levels of lithium in drinking water in Japanese males [140], in Japanese females [141] and significant effects in populations in Greece [142], Austria [143][144][145], and Texas [146], but no such effect in the east of England [147]. Systematic reviews and meta-analysis reports upheld the effectiveness of lithium in averting suicide, particularly associated with mood disorders [148][149][150][151][152].…”
Section: Pharmacological Management Of Suicidal Ideationmentioning
confidence: 99%
“…While the original research paper [9] applied contextual neural gas [16,17] to account for spatial autocorrelation [18], we complement this spatially explicit approach with a non-spatial analysis using widely applied self-organizing maps (SOMs) [19,20] (other options can be found in [21]). A SOM is an unsupervised artificial neural network for data clustering and visualization [19].…”
Section: Data Usage and Applicationmentioning
confidence: 99%